UJI EFEK ANALGESIK INFUSA DAUN CENGKEH (Syzygium Aromaticum (L.) Merr. & L. M. Perry) PADA MENCIT YANG DIINDUKSI ASAM ASETAT - Anggitasari, Wima (NHM PRESS, 2022)
Pain is one of the things that people often complain about, which causes patients to come to health facilities. Many studies related to the development of drugs from herbal plants have been carried out considering the efficiency of herbal plants and concerns about the side effects of chemical drugs. One of the plants that has the potential to be developed as an analgesic is Clove. This study is an experimental study with mice where the test animals were divided into 5 groups, namely group I (negative control), group II (positive control), group III (clove leaf infusion at a dose of 200 mg/kgBW), group IV (clove leaf infusion). dose of 400 mg/kgBW) and group V (clove leaf infusion at a dose of 800 mg/kgBW). This study uses the Writing reflex test method. From the results of data analysis, it is known that groups II, III, IV and V have significant differences with group I (negative control). The calculation of the percentage of protection showed that the infusion treatment group at doses of 200 mg/kgBW, 400 mg/kgBW and 800 mg/kgBW had a percentage of protection 50%. The conclusion of this study is that clove leaf infusion has the potential to be developed as an analgesic drug.